Current research into A20 mediation of allergic respiratory diseases and its potential usefulness as a therapeutic target - Liu, Yan; Xu, Kai; Yao, Yin; Liu, Zheng (Frontiers in Immunology, 2023)
The potent anti-inflammatory protein A20, termed tumor necrosis factor-α-inducible protein 3 (TNFAIP3), exerts its effects via inhibiting nuclear factor κB (NF-κB) signaling. A20 ubiquitin (Ub) editing abilities have recently garnered much attention, resulting in its identification as a susceptibility gene in various autoimmune and inflammatory disorders. Allergic airway disorders are defined by excessive and prolonged type 2 immune responses to inhaled allergens. Consistently activated NF-κB signaling involved in allergic airway diseases. Recently, several TNFAIP3 gene locus nucleotide polymorphisms have been correlated to allergic airway diseases, according to the results of genome-wide association studies. In addition, A20 is critical for immune regulation in childhood asthma, particularly for protection against environmentally mediated disease. A20-induced protective effects against allergy were observed in conditional A20 knockout mice in which A20 was depleted in lung epithelial, dendritic, or mast cell populations. Furthermore, A20 administration significantly decreases inflammatory responses in mouse models of allergic airway diseases. Here, we review emerging findings elucidating the cellular and molecular mechanisms by which A20 regulates inflammatory signaling in allergic airway diseases, as well as discuss its potential as a therapeutic target.